“ASLX”: Semantic Analyzer for programming languages based on XML - Buffa, Gabriela Yanel (2013)
XML (Extensible Markup Language) is a language used to structure information in a document or any file containing text. An XML document is "well formed" if respects their basic syntactic structure, that is composed of elements, attributes, and specified as XML comments. Some ways to verify that an XML file is either formed is by: Document Type Definition (DTD) and XML Schemas. But these types of verification not include relevant aspects, such as, the semantic relationship between content attributes and tags, declarations of fields and check the scope of variables, among others. This raises the need for a tool for verifying programming languages based on XML in the semantic aspect. In addition to analyzing the scope and usability of the tool was used as a case study the NCL declarative language.